PENTINGNYA PEMILIHAN STRATEGI PENGELOLAAN SUMBER DAYA MANUSIA DALAM PENCAPAIAN TUJUAN ORGANISASI - Kusmaningtyas, Amiartuti (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
Every organization even business oriented organization, social (foundation) organization, government organization and other social organization surely have a purpose to reach that become motivation to act.            Human resources’ role will be more appreciated especially in human resources competency in business management. Appreciation of human resources competency is needed because it will influence the effectivity of business activities.            The leading ability should be well controlled by manager, because without the leading ability which connected to human resources, the manager will imposible to reach the success.Keywords : Strategy of Human Resources Management, Competency,                    Professional Manager.